Improving survival: injury and mortality of fish struck by blades with slanted, blunt leading edges. Issue 2 (2nd July 2020) - Amaral, Stephen V.; Watson, Sterling M.; Schneider, Abraham D.; Rackovan, Jenna; Baumgartner, Andrew
Abstract: Compact turbines offer potential to reduce hydropower plant construction costs, but conventional turbine blade designs endanger entrained fish due to high blade strike speeds and thin leading edges. We evaluated the potential for combined blade leading edge slant and large leading edge thickness to increase strike survival. Rainbow trout ( Oncorhynchus mykiss ) were subjected to strikes with 100 mm thick blade analogues. At 10 m/s, strikes at fish length to blade leading edge thickness ratio (L/t) of 2 resulted in 98% survival at a location along the blade witha 30° slant relative to the tangential direction, compared to 26.8% survival at a location with 90°slant. For L/t 1.14-2, survival was found to be sensitive to location of strike within the mid-body region, determined from high-speed video. Strikes of 200 mm fish at 10 m/s resulted in 68% survival when body strike location was 0.58 (near caudal), and 7.9% when body strike location was 0.36 (near head). These results are consistent with previous trends and indicate opportunities to improve turbine blade design for greater entrained fish survival at higher turbine speeds, at both low head (<30 m) and high head projects.